Characterization and purification of pentameric chimeric protein particles using asymmetric flow field-flow fractionation coupled with multiple detectors - Kotoucek, Jan; Hezova, Renata; Vrablikova, Alena; Hubatka, Frantisek; Kulich, Pavel; Macaulay, Stuart; Roessner, Dierk; Raska, Milan; Psikal, Ivan; Turanek, Jaroslav (Analytical and bioanalytical chemistry, 2021)
Porcine circovirus causes the post-weaning multi-systemic wasting syndrome. Despite the existence of commercial vaccines, the development of more effective and cheaper vaccines is expected. The usage of chimeric antigens allows serological differentiation between naturally infected and vaccinated animals. In this work, recombinant pentameric vaccination protein particles spontaneously assembled from identical subunits-chimeric fusion proteins derived from circovirus capsid antigen Cap and a multimerizing subunit of mouse polyomavirus capsid protein VP1 were purified and characterized using asymmetric flow field-flow fractionation (AF4) coupled with UV and MALS/DLS (multi-angle light scattering/dynamic light scattering) detectors. Various elution profiles were tested, including constant cross-flow and decreasing cross-flow (linearly and exponentially). The optimal sample retention, separation efficiency, and resolution were assessed by the comparison of the hydrodynamic radius (Rh) measured by online DLS with the Rh values calculated from the simplified retention equation according to the AF4 theory. The results show that the use of the combined elution profiles (exponential and constant cross-flow rates) reduces the time of the separation, prevents undesirable sample-membrane interaction, and yields better resolution. Besides, the results show no self-associations of the individual pentameric particles into larger clusters and no sample degradation during the AF4 separation. The Rg/Rh ratios for different fractions are in good correlation with morphological analyses performed by transmission electron microscopy (TEM). Additionally to the online analysis, the individual fractions were subjected to offline analysis, including batch DLS, TEM, and SDS-PAGE, followed by Western blot.
Keywords: frakcionace tokem v poli; Mice; buněčné linie; Protein Multimerization; Recombinant antigen; Animals; myši; virové proteiny; rekombinantní fúzní proteiny; Cell Line; Theilovirus; Recombinant Fusion Proteins; Asymmetric flow field-flow fractionation (AF4); zvířata; Circovirus; Fractionation, Field Flow; multimerizace proteinu; Viral Proteins